Improved Ferroelectricity and Endurance of Hf0.5Zr0.5O2 Thin Films in Low Thermal Budget with Novel Bottom Electrode Doping Technology. Issue 24 (28th July 2022) - Tian, Guoliang; Xu, Gaobo; Yin, Huaxiang; Yan, Gangping; Zhang, Zhaohao; Li, Lianlian; Sun, Xiaoting; Chen, Jia; Zhang, Yadong; Bi, Jinshun; Xiang, Jinjuan; Liu, Jinbiao; et al.
Abstract: HfO2 ‐based ferroelectric memory is one of the most attractive candidates for embedded memory in future monolithic‐M3D integrated‐circuit (IC). However, ferroelectricity and endurance will degrade at lower annealing temperatures due to the limitation of the M3D‐IC in thermal budget, which significantly inhibits its potential for many applications. In this work, a novel process technology using As 5+ implantation (As‐imp) at the bottom electrode (BE) in TiN/Hf0.5 Zr0.5 O2 (HZO)/TiN capacitors is proposed. The HZO film shows excellent ferroelectricity and improves endurance at the annealing temperatures of 350 and 400 °C, especially when the dose of As‐imp is 1 × 10 16, where the endurance of the HZO film is up to 1.5 × 10 11, and the remnant polarization ( P r ) far exceeds the reference capacitor without BE As‐imp, where 2Pr is greater than 40 °C cm −2 after 1.5 × 10 11 cycles. The underlying physical mechanism is that the oxidation reaction of introduced As 5+ during the film deposition releases extra oxygen atoms to fill the oxygen vacancies ( V o ) near the BE interface due to the occurrence of the thermal reduction reaction in the subsequent annealing process. This study paves the way for the integration of HZO‐based ferroelectric embedded memory in future high‐performance and energy‐efficient 3D‐ICs. Abstract : The implantation of As ion at the TiN bottom electrode can enhance the ferroelectricity of Hf0.5 Zr0.5 O2 (HZO)‐based capacitors and improve the endurance in the low thermal budget of 350 °C and 400 °C, which may benefit the development of back‐end‐of‐line compatible nonvolatile ferroelectric embedded memory with high performance and reliability in M3D‐IC.